Sustainable Organic Waste Management for Village SDGs - Ilalfiah, Luluk; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2023)
This study employs a qualitative descriptive analysis method to investigate the sustainable management of organic waste in Ketapang Village, aligning with the Sustainable Development Goals (SDGs). Utilizing observation and interviews, the research applies Haris's theory to analyze economic, social, and environmental sustainability aspects. Findings reveal three key aspects: economic sustainability through the development of fruit-picking tourism, environmental sustainability via ecosystem preservation, and social sustainability by enhancing community skills. The study provides valuable insights into organic waste management, offering a reference for improving its quality and contributing to the broader objectives of sustainable development. Highlight : Economic Empowerment: The study emphasizes the development of fruit-picking tourism as a means to generate employment and economic benefits, contributing to the financial sustainability of Ketapang Village. Environmental Preservation: The research underscores the importance of organic waste management in preserving ecosystems, ensuring their sustainability to support present and future life in the village. Community Skill Enhancement: The study highlights the social sustainability aspect, focusing on the improvement of community skills, indicating a positive impact on local human capital and community development. Keywords: Sustainable Development Goals, Organic Waste Management, Ketapang Village, Economic Sustainability, Social and Environmental Impact.